Biologically recovered polyhydroxyalkanoates (PHA) as novel biofilm carrier for Acid Orange 7 decolourization: Statistical optimization of physicochemical and biological factors. (October 2022) - Chang, Jia Yun; Sudesh, Kumar; Bui, Ha Manh; Ng, Si Ling
Abstract: The incorporation of biofilm process in activated sludge process is beneficial in enhancing treatment performance. In this study, biologically recovered polyhydroxyalkanoates (PHA) were explored as an eco-friendly alternative to conventional materials as the biofilm carrier. The PHA was shaped in a pellet form, melt-fused and added as a biofilm carrier in a moving bed biofilm reactor (MBBR). From the scanning electron microscopy image, biofilm was successfully developed on the PHA pellets, with a biofilm thickness of 236 μm. Modeling and optimization were conducted using response surface methodology (RSM) in predicting the AO7 decolourization efficiency and first-order kinetics in the integrated biofilm and suspended activated sludge processes. The interaction effects of three factors of suspended activated sludge concentration (2000–6000 mg/L), PHA pellet packing volume (1–20 %) and initial AO7 concentration (1–20 mg/L) on AO7 decolourization were studied. The AO7 decolourization efficiency and kinetics were well described using the respective reduced quadratic regression models. The analysis showed that the AO7 decolourization was significantly affected by the suspended activated sludge concentration and the PHA pellet packing volume. Under the optimum conditions (5100 mg/L suspended sludge, 10 mg/L initial AO7 and 20 vol% of PHA pellets), the maximum AO7 decolourization efficiency and rate constant were 96.44 % and 0.3550 h −1, respectively. The high bioactivity of attached activated sludge at a low packing volume demonstrated the potential of the biologically recovered PHA as a biocarrier in retaining a high biomass concentration with a low space requirement. Graphical abstract: Unlabelled Image Highlights: Biological recovered polyhydroxyalkanoates (PHA) were employed as biofilm carrier. Mature biofilm with a thickness of 236 μm was developed on PHA. The biofilm on the PHA pellets exhibited high bioactivity for AO7 decolourization. The AO7 removal was affected by the amount of suspended and attached biomass. The AO7 decolourization efficiency and kinetics were optimized using RSM.